SC7 Neonatal simulation, the new fat burner for paediatric trainees?: effect of in situ high fidelity neonatal simulation training on the heart rate of neonatal trainees at a single tertiary nicu. (17th November 2016) - Boucher, Lucy; Daly, J; Dunlop, A; Ellis, S
Abstract : Background: An environmental stimuli creates a stress state the hypothalamic- pituitary-adrenal axis. 1 Cognitive literature demonstrates an inverted U relationship between stress and performance. Within paediatrics there is a risk of trainees becoming over stressed in emergencies due to their relative infrequency, 2 however simulation training can increase the acquisition of skills. 3 High fidelity patient simulation has the ability to recreate lifelike training conditions. Whilst the physiological stress response of trainees to simulation training has been assessed in some studies on adult resuscitation 4 few such studies have been conducted on trainees undertaking paediatric or neonatal simulation. Methods: Prospective pilot study of Paediatric trainees at a single tertiary NICU over 2 months in 2016 to assess feasibility of a larger study. Heart rate data was collected and analysed using a smart watch and app. Heart rate was recorded for 10 minutes prior to simulation, during simulation and the de-brief. Results: Average baseline heart rate was 66 bpm and maximal 124 bpm. Average rise of 61 bpm a 96% increase from baseline. An average of 3.6 minutes was spent in their fat burning zone and 1 minute in their cardio zone. An average of 18 minutes was spent with a heart rate above baseline from the start of simulation taking 8 minutes to return to baseline. Dips In heart rate were noted when more senior help arrived whereas inter-team conflict created rises in heart rate. Conclusions: This pilot study demonstrated that neonatal simulation provokes a measurable physiological response in paediatric trainees. There is scope to include all team members, compare data from simulation and "real life" resuscitation as well as expanding the biomarkers to include salivary cortisol, peripheral skin temperature and electro-dermal activation. Eventually data could help tailor simulations to target an optimum stress response improving team performance and learning to improve outcomes for real resuscitations. References: Timmermans W et al . Stress and excitatory synapses: from health to disease. ? Neuroscience . 2014;248 :626–36. Templeton J. A Review of the European Working Time Directive on the Quality of Training. A Report for Medical Education . England; 2010. Finan E, Bismilla Z, Whyte HE et al . High fidelity simulator technology may not be superior to traditional low fidelity equipment for neonatal resuscitation training. J Perinatol . 2012;32 :287–292. Clarke S, Horeczko T, Cotton D, Bair A. Heart rate, anxiety and performance of residents during a simulated critical clinical encounter: a pilot study. BMC Med Educ . 2014;14 :153.